Gender Issues in US Science and Technology Policy: Equality of What? - Cozzens, Susan E. (Science & Engineering Ethics, 2008)
Fairness in evaluation processes for women in science and engineering is only one of a set of issues that need to be addressed to reach gender equality. This article uses concepts from Amartya Sen’s work on inequality to frame gender issues in science and technology policy. Programs that focus on increasing the number of women in science and engineering careers have not generally addressed a broader set of circumstances that intersect with gender at various economic levels and stages of life. The agendas in research and innovation policies also need to reflect these issues, and fair allocation of resources within both science and technology needs to be on the agenda. Getting women into high-level positions is not enough. Articulating the full research and innovation agendas for women will require broader participatory processes.